Data Journalism, Digital Verification and AI. The Case for Newsroom Convergence - Laura Postma (VIEW Journal of European Television History and Culture)
This article discusses the opportunities and challenges of implementing data journalism, digital verification and AI in the centre of the newsroom. Data journalism, digital verification and fact-checking continue to be seen like jobs for specialists. As has AI, they have all entered newsrooms in various forms over the past two decades. This article comes out of preparatory work for an online course on data literacy for journalism, communication and creative industries students called MediaNumeric. The course focuses on search and exploration of data, digital skills, and tracking and debunking misinformation. As part of this special issue, this article wants to offer a sense of what is at stake in data entering newsrooms, and editorial and media production offices.